Estimando as elasticidades pobreza/renda/desigualdade no Brasil e suas regiões pós Plano Real - Campos, Henrique Câmara (2007)
Brazil is among the twenty greatest economies in the world. During the twentieth century, its GDP grew in average 4.9% per year. However, the country presented a high level of income inequality, which associated to the high poverty levels in its population, places it as a nation with serious social problems. This work, aims to analyze the relation between poverty, economical growth and income inequality, emphasizing the estimates of elasticity of the average income and the income concentration related to the poverty in Brazil and in its regions after the “Real” economical plan, attempting to identify which instrument is more efficient in the reductions of poverty levels: the increase of the average income or the decrease of inequalities. The methodology procedures used herein, were based on studies done by Ravallion and Chen (1997) and Adams Jr. (2004), using econometric models with data on panel. The proposed models use five indicators of poverty P(0) – Poverty Proportions, P(1)- Poverty Gap-P(2) Quadratic Gap, Index of SEN and Index of Watts, as dependent variables. Analyzing the elasticities, we notice that there is an indirect relation between poverty and the economical growth, considering that the same level of inequality is maintained, if there is economical growth there will be reduction in the index of poverty and a direct relation between poverty and inequality, therefore, the poverty will decrease. The obtained results reveal that the elasticity: poverty-inequality are greater than the elasticity: poverty income, and the regional differences are evidenced according to the level of poverty and inequality, detaching the northern and northeastern regions with lower indexes of elasticity.